Implication of Biological Activated Carbon Process Performance and Microbial Growth on Granular Activated Carbon for the Removal of Dissolved Organic Carbon in Water Purification - Hun Lim, Do; Jin Lee, Yoon; Song Ko, Young (Asian Journal of Chemistry, 2010)
This research was performed to choose a suitable activated carbon when a biological activated carbon process was applied and the removal efficiency of organic carbon with biological activated carbon was assessed. Samples of different origin, such as river, lake water and humic acid, using four different types of activated carbon were investigated. The highest removal of dissolved organic carbon was obtained with Cargon and Norit activated carbon for a sample of Han river water and humic acid, respectively. Powder activated carbon appeared to be more efficient at removing dissolved organic carbon than was granular activated carbon for the sample of Han river water. Examination of the apparent molecular weight distribution showed that organic material over 10,000 daltons was removed, while low molecular weight distribution under 1,000 daltons increased after treatment with activated carbon of the sample of Han river water. The breakthrough point for Picabiol and Norit activated carbon was reached faster than was that for Cargon and Samchully activated carbon. An increasing order for biomass formation on activated carbon was shown for Cargon, Picabiol, Samchully and Norit activated carbon, respectively.